Análisis de los insights en el proceso de compra del consumidor generacional; baby boomers, x, millennials, y z de la ciudad de Loja - Cuenca Cuenca, Mishell Joselyn (2023)
The consumer's mind is a universe to discover, which directly influences their purchasing behavior, which is why the main objective of this curricular integration work is to analyze the insights in the generational consumer purchasing process; baby boomers, x, millennials, and z from the city of Loja, to meet consumers, regarding their emotions, tastes, preferences, perceptions, and motivations, improving decision-making in terms of marketing strategies, since there is currently little information or there is a great lack of knowledge at the local level, by local companies, about the context of the purchasing behavior that consumers have according to their internal aspects that make them buy, being a serious problem for decision- making in lojanas companies, using marketing strategies regarding widespread advertising. A conclusive exploratory design was used, with a descriptive investigation and a simple cross- sectional design, through a survey of the inhabitants of the city of Loja, with data obtained from the INEC and projected to 2022, by age, from 18 to 75 years. having a population sample of 384 surveys, with a simple random probabilistic technique, managing to identify that the insights have a great influence on the citizens of Loja when buying, specifically in customer service with 64.10% in terms of perception and emotion, at the same time it is determined that each generation has its different preference variables when they buy, in relation to; technology, home, leisure, education, health, clothing and food. It was concluded that, if there is a direct relationship between the Insights and the consumer purchasing process, through a Chi-square test, where the null hypothesis is rejected and the alternate one is accepted.